Making centralised data work for community development: An exploration of area-based training programmes in a unified framework - Séamus McGuinness; Adele Bergin; Adele Whelana (The Economic and Social Research Institute (ESRI), 2017)
Data relating to community development activities is often decentralised in nature and does not easily facilitate any national level analysis. Given non-trivial spending in this area and increased pressure to show value for money in all areas of government expenditure, there is increased pressure for some measurement and assessment of community level spending. In Ireland, a single body, Pobal, co-ordinates a large proportion of community development activity under a national community development programme. The Local and Community Development Programme (LCDP) represented a central component of Ireland's funding for community development which aims to tackle poverty, social exclusion and long-term unemployment through local engagement and partnerships between disadvantaged individuals, community organisations and public sector agencies. This "bottom-up" structure aims to enable participation by citizens in the design, planning and implementation of interventions at a local level. Organisations in receipt of funding under LCDP must record their activities within a single database. The availability of this data provides a unique opportunity to address a number of key questions, in a unified framework, regarding community development spending that will help inform policy both in Ireland and elsewhere. Specifically, the paper explores the relationship between community development training and goals and the links between provision and social deprivation, geography and cost. It also considers the extent to which the general requirement to demonstrate value for money in the public finances could, and/or should, be extended into the community development realm.
Keywords: 330; Community Economic Development; Training Course Provision; Evaluation